Structure–property relationship study of blue thermally activated delayed fluorescence molecules with different donor and position substitutions: theoretical perspective and molecular design. Issue 12 (24th November 2021) - Song, Yuzhi; Li, Bihe; Liu, Songsong; Qin, Ming; Gao, Yang; Zhang, Kai; Lin, Lili; Wang, Chuan-Kui; Fan, Jianzhong
Abstract : Blue-efficient thermally-activated delayed fluorescence emitters are widely desired in organic light-emitting diodes due to their advantages in both improving display resolution and providing better pixels. Abstract : Blue-efficient thermally-activated delayed fluorescence emitters are widely desired in organic light-emitting diodes due to their advantages in both improving display resolution and providing better pixels. However, both the species and amounts of blue-TADF molecules are far from meeting the requirement for practical applications. Thus, systematic studies are desired to study the relationship between molecular structures and luminescent properties. Herein, a total of 15 molecules with different donor substitutions (DMAC, PXZ, PTZ, DPA and Cz) and different position substitutions ( ortho, meta and para ) are designed and their photophysical properties are studied in detail utilizing density functional theory (DFT) and time-dependent DFT methods. The conformational isomerization, intramolecular interactions, energy gaps, spin–orbit couplings, and fluorescence efficiencies are analyzed. Moreover, the radiative and non-radiative as well as the intersystem crossing (ISC) and reverse intersystem crossing (RISC) processes are investigated using the thermal vibration correlation function method. Results indicate that molecules with m -substitutions possess the largest energy gap between the lowest singlet and triplet excited states. However, molecules with DPA and Cz substitutions can bring remarkable spin–orbit coupling effects, excellent radiative decay rate and efficient ISC and RISC rates. By analyzing the calculated quantum efficiencies, five promising blue-TADF molecules ( o -DPA-QL, m -DPA-QL, p -DPA-QL, o -Cz-QL and m -Cz-QL) with stable nearly planar conformations are theoretically proposed. Our work gives reasonable explanations for experimental measurements and provides a molecular design strategy for efficient blue-TADF molecules.